Community Empowerment Based Tourism Village As an Effort to Increase the Potential of Jamu - Ambarwati, Diana; Wisnu Wardhana, Ludi; Nadhiroh, Umi; Wahyuarida, Ririn (KnE Social Sciences, 2020)
This study aims to determine the potential problems and solutions in community empowerment based on tourist villages and excellence with the existence of “Jamu” Tourism Village in Kampungdalem Village, Kediri City. This resarch used qualitative methods with approach Participatory. The main techniques of data collection are done through observation techniques (both physical data observation and observation involved), focus group discussions (FGD) and surveys directly to respondents from May to July 2019. Physical observation to find out problems in community empowerment based on “Jamu” Tourism Village with Citizens RW 02 Kampungdalem Village Kediri City. While observation is involved to identify solutions and benefits or advantages of “Jamu” Tourism Village with Village Chief and Public Relation. The sample this research are 30 people example Village Chief, Public Figure, Citizens around on local Kampungdalem Village Kediri City at FGD present. Identification of problems including residents having various fields of business other than herbal medicine, the quality of diverse tastes of each herbal medicine manufacturer, and the existence of an icon of Child Friendly Village before the existence of “Jamu” Tourism Village. The solution to this problem is the need for moral and material encouragement for people, the assistance and supervision of all herbal medicine producers, and uniting different icons into one interesting treat. The advantages are mature concepts based on clusters, variations of various processed herbal products, renting costume sellers and supporting properties, opening jobs and reducing crime rates and preserving the nation’s culture while maintaining a healthy body. Keywords: Community Empowerment, Tourism Village, Increased Potential, Traditional Herb